Effects of lithium chloride and methylprednisolone on experimental spinal cord injury - Ekici, Mehmet Ali; Ozbek, Zuhtu; Temel Incedal, Halide Edip; Colak, Omer; Arslantas, Ali; Baydemir, Canan (The European Research Journal, 2016)
Objective. Antioxidant effects of lithium chloride (LiCl) and methylprednisolone were investigated in an experimental spinal cord injury.Methods. Spinal cord injury was performed by cerebral vascular clip with a closing force of 40 g; the duration of epidural compression was 30 seconds after T9-11 total laminectomy in the rat spine. The study was conducted in 4 groups. Group 1: sham (n=8), group 2: 0.9% saline (n=8), group 3: LiCl (n=8), group 4: methylprednisolone (n=8). Ketamine (60 mg/kg) and 2% xylazine (5 mg/kg) were used intraperitoneally as anesthesia protocol for the groups. The rats were sacrificed 24 hours after the injury and blood samples were taken. Total oxidant status (TOS), total antioxidant status (TAS), malondialdehyde (MDA) and tumor necrosis factor-α (TNF-α) level were analyzed.Results. Median (q1-q3) levels of TAS, TOS, MDA and TNF-α were statistically analyzed for the study groups. The TAS values of LiCl yielded statistically significant differences compared with group 1, 2 and 4 (p